Collaborative Leadership of the Subdistrict Head’s in Addressing Authority Vacuum in Flood Management in East Teluk jambe Timur Subdistrict: Kepemimpinan Kolaboratif Camat Dalam Mengatasi Kekosongan Otoritas Penanganan Banjir Di Kecamatan Telukjambe Timur - Riska Setyanti Solihat; Eka Yulyana (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study analyzes the collaborative leadership of the Head (Camat) of Telukjambe Timur Subdistrict in addressing the authority vacuum arising from fragmented flood management responsibilities across multiple government levels and actors. Design/Methodology/Approach: Using a qualitative approach with an embedded single-case study design (Yin, 2018), primary data were collected through in-depth interviews with six informants during March–April 2026, supplemented by secondary data from government documents and media coverage. Data were analyzed using the explanation-building technique within Archer and Cameron's (2013) Collaborative Leadership framework. Findings: The Camat's leadership proved effective during the emergency response phase across three dimensions: building relationships, supported by an informal Forkopimcam network; handling conflicts, which successfully defused operational tensions at the evacuation center; and sharing control, through role distribution with BPBD and the Social Affairs Department. However, this effectiveness did not extend to structural mitigation—the conflict between Wadas and Purwadana villages over water channel normalization was resolved only through external intervention, exposing the real limits of the Camat's authority. Practical Implication: The study recommends that the Karawang Regency Government optimize authority delegation to district heads, activate the district-level Disaster Risk Reduction Forum (PRB) under Regency Regulation No. 45 of 2025, and integrate disaster mitigation planning into district-level Musrenbang processes. Originality/Value: This study fills an empirical gap in Indonesian disaster governance literature by examining collaborative leadership at the meso-government (district) level within a complex industrial area—a dimension not yet specifically explored in prior research. Paper type: Research Paper